EFL learners’ Procrastination in Completing Academic Writing Tasks: The Factors and Its Possible Effects - Jarum Jarum; Dinda Ayudiari (Institut Agama Islam Negeri Palopo, 2022)
Recently, procrastination has become one of the crucial problems for many students. This can affect the learning outcomes. Responding to that issue, this study was conducted to investigate procrastinating behavior encountered by the English Department students during their Academic Writing task completion. It investigates (1) the factors contributing to students’ procrastination in completing their tasks, and (2) the effects of students' procrastination on their achievement. Qualitative research design was applied. Thirty EFL learners of English Language Education Department in one of Indonesian private university participated in this research. To collect the data, questionnaire was used in the form of closed-ended and open-ended questions. From the collected data, it was found out that the students' procrastination was influenced by two major factors; internal and external. The internal factors include perfectionism, self-regulation failure, low self-efficacy, sensation seeking, lack of motivation and laziness. Meanwhile, the external factors include family background, social environment, task characteristic, distraction, another task completion, and device. In addition, procrastination has caused several effects for the students; they are health issues, decreasing productivity, losing opportunities, self-regret, losing self-confidence and a fear of getting a low score. The pedagogical implications of the research findings are further elaborated and recommendations for future work are highlighted as well.